The Regulatory Role of Long Noncoding RNAs in Different Brain Cell Types Involved in Ischemic Stroke - Chen, Runsen; Xu, Xiangming; Huang, Lidan; Zhong, Wangtao; Cui, Lili (Frontiers in Molecular Neuroscience, 2019)
Stroke results in high morbidity and high mortality worldwide, with ischemic stroke accounting for 80% to 85%. As effective treatments for ischemic stroke remain limited because of the narrow therapeutic time window, a better understanding of the pathologic mechanism and new therapeutic intervention targets are needed. Due to the development of next-generation sequencing technologies and genome-wide analysis of eukaryotic transcriptomes, a large amount of evidence to date demonstrates that lncRNAs play a vital role in gene regulation and in ischemic stroke. In recent years, many studies have been focusing on the clinical significance of lncRNAs in ischemic stroke, and data show that the pathological processes underlying ischemic stroke are driven by interaction among different brain cell types, including neurons, glial cells and vascular cells, which actively participate in the mechanisms of tissue injury and repair. In this review, we provide an overview of the characteristics and underlying regulation mechanisms of lncRNAs relevant to different brain cell types during the course of ischemic stroke. Moreover, we reveal the roles of lncRNAs as potential biomarkers and treatment targets in ischemic stroke.